Bridging Traditional Arabic Pedagogy and AI-Supported Learning through Snakes and Ladders Game-Based Instruction - M. Naufal Al Qurthuby Fuady S; Halimi Zuhdy; Idrus Muchsin bin Agil (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study explores the use of snakes and ladders game-based instruction in Arabic uslub learning at LSBA Ula within the broader perspective of AI-supported pedagogy. The study emerged from the challenges of contextual Arabic language learning, particularly students’ difficulties in understanding the communicative functions and contextual usage of Arabic expressions through conventional teacher-centered instruction. Using a qualitative case study approach, data were collected through classroom observation, semi-structured interviews, and learning documentation involving students and teachers participating in Arabic uslub instruction. The findings reveal that the traditional snakes and ladders game created collaborative and contextual learning interactions through peer discussion, meaning negotiation, reflective feedback, and experiential learning activities. The study also found that the pedagogical mechanisms emerging during gameplay, including real-time feedback, error identification, and adaptive instructional support, align with the principles of AI-supported learning without transforming the traditional game into a digital AI-based system. This study concludes that traditional game-based instruction remains pedagogically relevant for Arabic language learning in the AI era because it supports collaborative, reflective, and human-centered learning experiences. The study contributes to the development of low-tech yet AI-compatible Arabic pedagogy, particularly in non-formal educational contexts.